One track mind - Cheong, Mark Benedict Tuck Fai (2017)
One Track Mind centers around the story of model railway enthusiast Thomas Bhat, and the friends he has made along the way. These men (henceforth referred to as Train Buddies) come from all walks of life - a retired banker, a retired handyman, an advertiser, an engineer, and an IT consultant - but they share a roaring passion for their locomotives. In 13:17 minutes, One Track Mind explores how these miniature models captivate the men, and the lengths people will go for the things they love - even if no one else understands.